Jinnah's Pakistan : Formation and Challenges of a State - Dar, Farooq Ahmad (Karachi Oxford University Press., 2014)
Analyzes the role played by the first Governor General of Pakistan. Based on primary source material, highlights his political, social, economic, and diplomatic contributions, and evaluates whether he exceeded constitutional limits when he exercised executive powers
Include Appendix, Bibliography and Index
Keywords: Pakistan -- Politics and government -- Jinnah, Mahomed Ali, 1876-1948